ENDOSCOPIC TUBAL CANALIZATION AS AN ALTERNATIVE TO IVF: AN OUTCOME ANALYSIS - RAHIM , A; RASHEED , M; RASHEED , T; SAJJID , A (Biological and Clinical Sciences Research Journal, 2024)
Tubal infertility is a significant contributor to subfertility worldwide, particularly in low- and middle-income countries like Pakistan, where limited access to advanced reproductive technologies poses significant challenges. Endoscopic tubal canalization offers a minimally invasive and cost-effective alternative to in vitro fertilization (IVF) for managing proximal tubal occlusion. Objective: This study aimed to evaluate the efficacy and safety of endoscopic tubal canalization as an alternative to IVF, focusing on procedural success rates, pregnancy outcomes, and associated complications in women with proximal tubal infertility. Methods: A prospective cohort study was conducted on 72 women of reproductive age diagnosed with proximal tubal occlusion using hysterosalpingography (HSG) or laparoscopy. Patients underwent endoscopic tubal canalization, and outcomes were assessed in terms of procedural success (unilateral or bilateral tubal patency), pregnancy rates (spontaneous and intrauterine insemination), and complications. Statistical analysis was performed to compare results with existing literature and evaluate the safety profile. Results: The overall success rate of tubal canalization was 83.3% (60/72), with unilateral patency achieved in 29.1% (21/72) and bilateral patency in 54.1% (39/72). The failure rate was 16.6% (12/72). The procedure was associated with a low complication rate, with only 4% (3/72) of patients experiencing tubal perforation. Pregnancy success was observed in 29.1% (21/72) of patients, with 52.3% (11/21) achieving spontaneous conception and 47.6% (10/21) conceiving via intrauterine insemination. Among pregnancies, 90.4% were intrauterine, while 9.5% were ectopic. The findings align with international studies, demonstrating comparable success rates and safety profiles. Conclusion: Endoscopic tubal canalization is an effective and safe alternative to IVF for managing proximal tubal infertility in resource-limited settings. It provides a cost-effective solution with favorable success rates and minimal complications, particularly for patients with socioeconomic constraints. This study contributes valuable data specific to the Pakistani population and highlights the need for further research to assess long-term outcomes and live birth rates.